2013
DOI: 10.1093/nar/gkt1163
|View full text |Cite
|
Sign up to set email alerts
|

DNA transposition by protein transduction of the piggyBac transposase from lentiviral Gag precursors

Abstract: DNA transposon-based vectors have emerged as gene vehicles with a wide biomedical and therapeutic potential. So far, genomic insertion of such vectors has relied on the co-delivery of genetic material encoding the gene-inserting transposase protein, raising concerns related to persistent expression, insertional mutagenesis and cytotoxicity. This report describes potent DNA transposition achieved by direct delivery of transposase protein. By adapting integrase-deficient lentiviral particles (LPs) as carriers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 44 publications
(58 reference statements)
1
40
0
Order By: Relevance
“…This may for example result in variable copy numbers of inserted transposon vectors. 47 Heavily transfected cells are likely to undergo the intended genetic modification, but may also sustain the production of the genome tool for days. In our hands, activity of piggyBac transposase encoded by plasmid transfected into human cells lines can be detected up to 14 days This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Plasmid Dna As a Source Of Genome-modifying Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…This may for example result in variable copy numbers of inserted transposon vectors. 47 Heavily transfected cells are likely to undergo the intended genetic modification, but may also sustain the production of the genome tool for days. In our hands, activity of piggyBac transposase encoded by plasmid transfected into human cells lines can be detected up to 14 days This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Plasmid Dna As a Source Of Genome-modifying Enzymesmentioning
confidence: 99%
“…110 Our own endeavors to develop lentiviral protein transduction for genome engineering were directed first at incorporating the hyperactive piggyBac transposase hyPBase 113 in lentiviral particles. 47 A schematic representation of this approach is provided in Figure 2. Using the packaging construct design developed by Aoki et al, 103 we fused hyPBase to the N-terminal end of Gag and separated the two domains with a HIV-1 protease cleavage motif.…”
Section: Adapting Lentiviruses For Direct Protein Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…One possible way to overcome this limitation is to use non-integrating lentiviral vectors to deliver both the transposon and the transposase. This type of system has been successfully implemented in primary human cells to drive transposition using the PB system [53]. Of note, when this system was compared to electroporation delivery, it was demonstrated that transfected cell populations contained cells with multiple integration events, while virally transduced populations contained cells with only a single integration event.…”
Section: Transposonsmentioning
confidence: 99%
“…Of note, when this system was compared to electroporation delivery, it was demonstrated that transfected cell populations contained cells with multiple integration events, while virally transduced populations contained cells with only a single integration event. This was likely due to the much lower level of transposase expression achieved with the viral delivery system [53,54]. While the efficiency of this system is still significantly lower than gene delivery using an integrating viral vector, the ability to limit integration events to one per cell will reduce the potential for genotoxicity in target cells.…”
Section: Transposonsmentioning
confidence: 99%